Personal Selling Communication Strategy of Retail Assistants in Building Customer Satisfaction at Eiger Basuki Rahmat Surabaya Store - Siti Mujanah; Novan Andrianto; Rafandi Budiaji Aryasa (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study aims to describe the interpersonal communication applied by retail assistants in personal selling activities at the Eiger Basuki Rahmat Surabaya Store. The research is motivated by the importance of interpersonal communication in building positive relationships with customers, understanding their needs, providing clear product information, and creating a comfortable shopping experience. The study employs a descriptive qualitative method with data collection techniques including in-depth interviews, observation, and documentation. Research informants consisted of retail assistants as primary informants and customers as supporting informants, while data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings reveal that retail assistants apply interpersonal communication effectively through both verbal and nonverbal communication. Verbal communication is conducted by conveying product information clearly, using easily understood language, and exploring customer needs. Meanwhile, nonverbal communication is demonstrated through smiles, eye contact, and friendly attitudes that create comfort. Retail assistants also demonstrate empathy and active listening skills before providing appropriate product recommendations. The study concludes that friendly, informative, and responsive interpersonal communication plays a significant role in personal selling activities.